EDUKASI HIPERTENSI MELALUI LEAFLET “TAAT DAN CERMAT” TERHADAP PERUBAHAN PENGETAHUAN LANSIA DALAM PENGELOLAAN HIPERTENSI - Wisnu Cahyo Prabowo; Zufiha Citra Utami Masdar; Yusuf Isro’ Ridhotulloh; Nur Viva Favorit (Jurnal Abdi Insani, 2026)
Hypertension is a non-communicable disease (NCD) that often occurs in the elderly. This disease can lead to serious complications if not properly managed. Increasing public knowledge, especially among the elderly, is a strategic step in promotive and preventive efforts to control hypertension. This community service activity aims to increase the elderly's knowledge regarding hypertension management through education using leaflets based on the behavior of "OBEYING and BEING CERMAT." Method: A pretest was conducted on 20 respondents at the Temindung Community Health Center in Samarinda. The leaflets provided information on hypertension, covering risk factors, causes, symptoms, consequences, and lifestyle modifications through the behavior of "OBEYING and BEING CERMAT." A posttest was then conducted to assess the effectiveness of the education provided. Results: A significant increase in respondents' knowledge level, from 10% to 75%, was observed in the good category. Education through leaflets has proven effective in delivering easily understood health information and can increase elderly awareness of independent and sustainable hypertension management. This information is concise and easily understood by the elderly to encourage change.